Alat Monitoring Kehadiran Karyawan WPK Dengan Smartcard RFID Berbasis IOT Via Web Xampp - Zaenal Abidin; Alwi Mahatir (FORTEI Regional VII Jawa Timur, 2022)
Technological developments are currently increasing rapidly, such as providing digital attendance monitoring facilities in the employee attendance process. The current research is the design of an attendance monitoring tool by utilizing the Radio Frequency Identification (RFID) Reader and Smartcard as identification for each employee. The application of technology in the development of attendance monitoring is very helpful to facilitate data collection of employees who have attended. Making this monitoring tool based on realtime can reduce employee delays in coming to and from work because they have their own smartcards that are used as attendance media. In this design research, this research is carried out based on IoT using phpmysqli with a website display that is made which consists of NodeMCU ESP 8266, RFID Module RC-522, LCD I2C 16x2, Buzzer and localhost as data storage in PhpMyAdmin.